ANALISIS MINAT MASYARAKAT TERHADAP PRODUK DIGITAL PEGADAIAN SYARIAH DALAM KEMUDAHAN BERTRANSAKSI DI PT. PEGADAIAN SYARIAH CPS ARIEF RAHMAN HAKIM - Tari Nopita Pratiwi; Chuzaimah Batubara; Sri Ramadhani (Lembaga Pengembangan Kinerja Dosen, 2025)
Pegadaian Syariah CPS Arief Rahman Hakim is a sharia financial institution engaged in financial services and other services that have main products of pawn financing and micro financing. This study aims to determine the Strategy and Obstacles of PT Pegadaian Syariah CPS Arief Rahman Hakim in providing convenience for customers to transact, and to find out how the public responds and interests in digital pawn service products. The approach to this research is Qualitative descriptive, with data collection methods, namely: interviews as supporting using documentation studies in accordance with the problems discussed. The results of the study concluded that PT Pegadaian Syariah CPS Arief Rahman Hakim implemented a strategy to provide convenience for customers in transacting using digital pawn products. PT Pegadaian Syariah CPS Arief Rahman Hakim is also still lacking in socialization, causing many local people who do not know about the existence of the digital pawnshop sharia product. The obstacles faced by PT Pegadaian Syariah CPS Arief Rahman Hakim in increasing the number of customers using digital products are triggered by the application system which often errors, do not have smartphones and prefer to come directly to the outlet.